2016
DOI: 10.1007/s12035-016-9843-0
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Rescues a PINK1 Knock Down SH-SY5Y Cellular Model of Parkinson’s Disease from Mitochondrial Dysfunction and Cell Death

Abstract: Parkinson's disease (PD) is a neurodegenerative disorder characterised by the loss of dopaminergic neurons in the substantia nigra. Mutations in the PINK1 gene result in an autosomal recessive form of early-onset PD. PINK1 plays a vital role in mitochondrial quality control via the removal of dysfunctional mitochondria. The aim of the present study was to create a cellular model of PD using siRNA-mediated knock down of PINK1 in SH-SY5Y neuroblastoma cells The possible protective effects of curcumin, known for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(44 citation statements)
references
References 36 publications
1
43
0
Order By: Relevance
“…Also, previous investigations have shown that CUR neuroprotective properties in in‐vitro and in‐vivo PD models are consistent with several different environmental factors …”
Section: Introductionsupporting
confidence: 70%
“…Also, previous investigations have shown that CUR neuroprotective properties in in‐vitro and in‐vivo PD models are consistent with several different environmental factors …”
Section: Introductionsupporting
confidence: 70%
“…109 Pretreatment with 4 improves mitochondrial membrane potential, oxygen consumption rates, and survival in cellular models of Parkinson disease. 110 Compound 4 attenuates neuronal death and reduces infarct size following cerebral ischemia-reperfusion injury with concomitant increases in mitochondria and improvements in neurological function. 111 In animal models of metabolic syndrome, 4 restores hepatocyte mitochondrial function to reduce hepatosteatosis.…”
Section: Natural Productsmentioning
confidence: 99%
“…In the dopaminergic cell lines MES23.5 and SH-SY5Y, curcumin treatments attenuated the neurotoxicity of 6-OHDA and improved cell viability by inhibiting increases in ROS levels, mitochondrial protection, and reducing p53-mediated apoptosis [ 22 , 23 ]. A recent study also reported that curcumin protected against mitochondrial dysfunction and cell death in PINK1 knockdown SH-SY5Y cells [ 24 ]. Moreover, curcumin had the potential not only to increase lifespan and locomotor abilities but also to decrease oxidative stress and DA neuron degeneration in rotenone-induced and human α -synuclein-expressing Drosophila models of PD [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%